2015
DOI: 10.1186/s13014-015-0503-8
|View full text |Cite
|
Sign up to set email alerts
|

Current state of the art of regional hyperthermia treatment planning: a review

Abstract: Locoregional hyperthermia, i.e. increasing the tumor temperature to 40–45 °C using an external heating device, is a very effective radio and chemosensitizer, which significantly improves clinical outcome. There is a clear thermal dose-effect relation, but the pursued optimal thermal dose of 43 °C for 1 h can often not be realized due to treatment limiting hot spots in normal tissue. Modern heating devices have a large number of independent antennas, which provides flexible power steering to optimize tumor heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
106
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(113 citation statements)
references
References 110 publications
(131 reference statements)
0
106
0
1
Order By: Relevance
“…Thus, heating methods that allow for local adjustment of the temperature distribution are preferred, such as radiative heating using a phased array of multiple antennas [70]. Radiative heating also allows for HT treatment planning [71][72][73][74], which may yield better temperature distributions and the possibility to avoid hot spots. With temperature being heterogeneous and not constant in time, reporting is preferably done using a set of thermal dose parameters [69].…”
Section: Thermal Dosimetrymentioning
confidence: 99%
“…Thus, heating methods that allow for local adjustment of the temperature distribution are preferred, such as radiative heating using a phased array of multiple antennas [70]. Radiative heating also allows for HT treatment planning [71][72][73][74], which may yield better temperature distributions and the possibility to avoid hot spots. With temperature being heterogeneous and not constant in time, reporting is preferably done using a set of thermal dose parameters [69].…”
Section: Thermal Dosimetrymentioning
confidence: 99%
“…Treatment planning is essential to optimise the radiation dose and temperature delivered to the tumour while minimising the risk of normal tissue complications. Currently, treatment planning for these two modalities is always performed separately, without taking the synergistic action between the two modalities into account [3][4][5][6]. Because of the synergy, treatment outcome strongly depends on the radiosensitising effect of the temperature distribution on the radiotherapy dose distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there were many reviews about hyperthermia randomized trials and indicated that it can enhance the efficacy of both radiotherapy and chemotherapy, and also many non-and randomized clinical trials have demonstrated the significant improvement in clinical outcome from adding hyperthermia to standard treatment regimens of radiation and/or chemotherapy [26][27][28][29][30][31][32][33][34] . Maluta, et al 37,38) .…”
Section: - -mentioning
confidence: 99%